IDENTITY OF MODERN ARCHITECTURE IN HISTORICAL CITY ENVIRONMENTS - Raffaele Gambassi (Architecture and Engineering, 2016)
The debate on the modern architectural project in the historical city is one of the most interesting subject in our society. Architecture represents the cultural imprint of an age and from the care of the cities and territories is possible to judge the quality of a govern. The historical buildings has created our magnificent urban landscapes, result of different visions of city during the passing of time. The feeling of respect for this heritage is a duty towards the previous generations and an teaching to express the sign of our time as they did in the past, without fears but with a great awareness of the importance to leave the imprints of our culture in the history. The paper considers the different approaches of modern architecture when it faces the historical environments and outlines interesting conclusions.